1997
DOI: 10.1093/oxfordjournals.eurheartj.a015410
|View full text |Cite
|
Sign up to set email alerts
|

Streptokinase vs alteplase in massive pulmonary embolism: A randomized trial assessing right heart haemodynamics and pulmonary vascular obstruction

Abstract: These results proved that, when the full dose of streptokinase has been given over 12 h, its efficacy is as good as that of 2 h of recombinant tissue plasminogen. A further trial aimed at comparing recombinant tissue plasminogen activator and streptokinase infused over a 2 h period is needed to determine whether a similar efficacy can be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 17 publications
0
53
0
9
Order By: Relevance
“…In the majority of survivors, thrombolysis as well as anticoagulation alone causes regression of clinical and echocardiographic symptoms of RV overload within 3-6 weeks. 4,9 In addition, pulmonary angiographic studies revealed that in most cases of APE the resolution of thromboemboli occurred within 21 days. 5 However, it was reported that in some patients after APE, residual perfusion defects could be detected by control lung scintygraphy or spiral computer tomography even in spite of adequate long-term treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of survivors, thrombolysis as well as anticoagulation alone causes regression of clinical and echocardiographic symptoms of RV overload within 3-6 weeks. 4,9 In addition, pulmonary angiographic studies revealed that in most cases of APE the resolution of thromboemboli occurred within 21 days. 5 However, it was reported that in some patients after APE, residual perfusion defects could be detected by control lung scintygraphy or spiral computer tomography even in spite of adequate long-term treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from RCTs, reporting on patients with massive [49][50][51][52][53][54] and submassive 52,55 PE, favour thrombolysis over heparinization. Randomized controlled trials comparing streptokinase and alteplase, in massive PE, 56,57 and urokinase and rTPA 58 failed to demonstrate superiority of one thrombolytic over another. The major risks associated with pulmonary thrombolysis include bleeding, hematoma formation at puncture sites, and intracranial hemorrhage, with intracranial hemorrhage occurring in approximately 2% of patients, ensuing up to 14 days following thrombolysis.…”
Section: Systemic Thrombolysismentioning
confidence: 99%
“…SK is used as an effective and inexpensive thrombolysis medication in some cases of myocardial infarction (heart attack) (Sikri and Bardia, 2007) and pulmonary embolism (Meneveau et al, 1997). The plant represents an enormous reservoir of biologically active compounds with various chemical structures and protective/disease preventive properties (phytochemicals).…”
Section: Introductionmentioning
confidence: 99%